TYPOLOGY OF PREFIXES IN FRENCH (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
The typology of prefixes on a semantic plan has not been highlighted enough because they are not theorized to their true extent. Therefore, this article proposes a study of the types of prefixes in French according to the Corbin’s (1991 and 2001) semantic and associative model. In order to do this, we have analyzed the meaning of the prefixes in five hundred prefixed words extracted from the French encyclopedic dictionary Le Petit Larousse illustré (2016). This study exposes various types of prefixes, most of which indicating the manner, the intensity, the place, the time, the frequency, the number, the total, the reduction, the deprivation, the quality, the attack, the defense, the protection, the possession, the cause, the consequence, the intention, the similarity, and the opposite. The prefixed word covers up the summary of a phrase and can be considered as a syntactical operation.